Cardiorespiratory fitness and body mass index on metabolic syndrome in middle-aged Japanese adults under national health guidance: a cross-sectional study - Xiangyu Zhai; Susumu S. Sawada; Sayaka Kurosawa; Sakura Koriyama; Serena A. Dimitroff; Shinji Sato; Yuko Oguma; Yoshio Nakata; Kazushi Maruo; Motohiko Miyachi; Yuko Gando; Koichiro Oka; et al. (BMC, 2024)
Abstract Objectives Poor cardiorespiratory fitness (CRF) and high body mass index (BMI) increased the risk of developing metabolic Syndrome (MetS) mostly in Caucasians. However, the sex-specific combined association of CRF and BMI on MetS considering health-related behaviors has yet to be thoroughly examined in Japanese. This study aims to investigate the sex-specific independent and combined associations of CRF and BMI with MetS in middle-aged Japanese adults. Methods 421 participants were included in this cross-sectional study. CRF was estimated using a submaximal cycle ergometer. CRF and BMI were respectively divided into three categories according to tertile distribution. MetS was diagnosed based on five risk factors: waist circumference, triglycerides, high-density lipoprotein cholesterol, blood pressure, and fasting glucose. Multivariable logistic regression models were used to estimate independent and combined association of CRF and BMI with MetS. Results Results showed that 154 (57.5%) and 70 (45.8%) of men and women had MetS, respectively. Compared to men with lower CRF or higher BMI, men with middle and higher CRF or middle and lower BMI were less likely to have MetS. Compared with 'unfit and higher BMI' group, 'unfit and lower BMI', 'fit and higher BMI', and 'fit and lower BMI' groups in men showed statistically significant decreased prevalences of MetS. However, no significant associations were found in women. Conclusions This study found significant independent and combined associations of CRF and BMI with MetS only in men, but not in women. However, prospective studies are warranted to confirm sex-specific associations of CRF and BMI with MetS.